Manajemen Pendidik dan Tenaga Kependidikan Disekolah - Aswaruddin, Aswaruddin; Hayati, Isma; Ramadhani, Jelita; Berutu, Khairani; Damanik, Aulia Rahmi; Marpaung, Wardatun Thaibah; Sihombing, Hulga Ryan Shori (STAI Denpasar Bali, 2024)
Management of teaching and educational staff is an activity that must be carried out starting from teaching and educational staff entering educational organizations until it finally stops going through the process of HR planning, recruitment, selection, placements, granting of champancies, awards, education and training development and termination. Management of educational personnel (teachers andemployees) absolutely must be implemented by the school principal in order to make use of it educational staff effectively and efficiently to achieve optimal results. In accordance with this, a school principal must be able to search for, positioning, evaluating, directing, motivating and developing talent every teacher and employee and is able to align individual and organizational goals